The Portraits Of Two Different Social Milieus Depicted In The Pariban: Idola Dari Tanah Jawa Movie - Sihombing, Lambok Hermanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2022)
The movie of “Pariban: Idola dari Tanah Jawa” shows the setting of a metropolitan city, Jakarta and the beauty of Samosir Island in North Sumatra. The use of language uttered by the main character, Halomoan Brandon Sitorus who lives in Jakarta is totally different from his relatives who live in his hometown, North Sumatera. In this scientific article, the author aims to observe how the camera works and the dialogue contributes to our understanding of Halomoan’s life in his hometown on the contrary to his life in the city. In order to help the author doing this analysis, the author first watch and identify every scene and shot of the movie and then collect the data that could help author for the analysis. To help with the analysis, Mise En Scene approach from Manon de Reeper and Theory of Representation from Stuart Hall are used for this study. The result of this study shows that this film represents the portraits of two different social milieu, Jakarta and Samosir Island. What the major character portrays in the movie through the scene and dialogue represent the different condition and reality of two compared cities.